Development of a multifingered robotic hand with the thenar grasp function. (18th May 2020) - Yoneda, Tomoo; Morihiro, Daiki; Ozawa, Ryuta
ABSTRACT: Manipulation of objects after grasping is an important research topic for robotic hands. In this research, we propose a grip method based on the thenar opposition, which is rarely handled in the framework of conventional precision and power grasps and useful in withdrawing a large torque after the grip, and develop a robotic hand that can realize the grasp as well as normal grasps. To this end, we propose methods to evaluate the thenar opposition and the variety of grasps based on the joint alignment of the thumb. Based on these methods, we determine the kinematic structure of the robotic hand and develop it with gear train transmissions and a soft skin. Experiments are implemented to demonstrate that the robotic hand realizes various grasps and a gripping force sufficient to withstand the torque that opens tightly clamped hand valves. GRAPHICAL ABSTRACT: